Monitoring the prevalence of the parasitic dinoflagellate Hematodinium sp in snow crabs Chionoecetes opilio from Conception Bay, Newfoundland - Pestal, GP; Taylor, DM; Hoenig, JM; Shields, Jeffrey D.; Pickavance, R (Diseases of Aquatic Organisms, 2003)
Bitter crab disease (BCD) of snow crabs Chionoecetes opilio is caused by a parasitic dinoflagellate, Hematodinium sp. In Newfoundland's commercial fishery, infected snow crabs are identified using visual, macroscopic signs of disease for separation prior to processing. We estimated the sensitivity and specificity of gross, macroscopic diagnosis of Hematodinium sp. by comparing these results with microscopic examination of prepared hemolymph smears. The sensitivity of a diagnostic test is the probability that the test will yield a positive result given that the animal has the disease. The specificity is the probability of a negative result given the animal is not diseased. In October 1998, we conducted a design-based survey using cluster sampling in 2 strata. Over 10 000 snow crabs from pot and trawl surveys were examined macroscopically for BCD. In addition, over 350 crabs were randomly examined microscopically for disease. The double sampling resulted in an estimated sensitivity of 52.7% and an estimated specificity of 100%. That is, a positive result from macroscopic examination is definitive, if the observer is well trained, but macroscopic examination will fail to detect infections in crabs with borderline clinical signs of disease. The prevalence estimated from macroscopic observations ((p) over cap (st) = 2.24%) was corrected for misclassification by dividing (p) over cap (st) by the estimated sensitivity (0.527), giving a corrected estimate of 4.25%. The use of double sampling provides for efficient estimation of prevalence in that large numbers of crabs can be quickly examined for gross signs of infection and the results corrected for misclassification based on a limited number of observations with a better, but time-consuming test. In addition, the prevalence of macroscopically infected male crabs was lower in a trap survey (0.57%) compared to a trawl survey (1.59%). In the trawl survey, female crabs had a significantly higher prevalence of macroscopically diagnosed infections than males (6.34%). The ...